Skin mini-erosion technique for monitoring metabolites in interstitial fluid: its feasibility demonstrated by OGTT results in diabetic and non-diabetic subjects. - Svedman, C; Samra, J; Clark, M; Levy, J; Frayn, K (1999)
The aim of this study was to evaluate a new interstitial fluid (IF) sampling technique and its application in diabetology. IF and venous whole blood were sampled serially during an oral glucose tolerance test (OGTT) on days 1 and 3 after formation of a mini-erosion in eight non-diabetic controls and eight Type 2 diabetic subjects. Glucose, lactate, glycerol, 3-hydroxybutyrate and insulin were assayed in IF and plasma. With solitary exceptions, the IF sample volumes were in excess of those required for measurement of all five substances. However, mean IF sampling rates differed significantly both between the non-diabetic and diabetic groups and between days 1 and 3 (p < 0.001 in all cases). In both groups, the OGTT curves of glucose, glycerol and 3-hydroxybutyrate were similar to the respective curves for plasma, whereas for lactate concentrations they were markedly greater in IF than in plasma (40% and 93% in the control group and 57% and 100% greater in the diabetic group on days 1 and 3, respectively). The reverse was true of insulin concentrations in the non-diabetic group, which were 57% and 74% lower in IF than in plasma on days 1 and 3, respectively. In the non-diabetic group, the baseline (pre-OGTT) insulin level in IF increased from 49 +/- 22% (SD) of that in plasma on day 1 to 74 +/- 19% of that in plasma on day 3 (p=0.005). Sampling site re-epithelialization was rapid. In conclusion, the feasibility of transdermal sampling of IF via a skin mini-erosion has been demonstrated in both diabetic and non-diabetic subjects.